Prospects of multipurpose biomonitoring for fisheries assessment based on environmental nucleic acids - Ana Ramón‐Laca; Krista M. Nichols; Kim M. Parsons; Ramón Gallego; David R. Vieites; Ignacio Doadrio; Ana Riesgo (Journal of Fish Biology, 2026)
Methods using environmental nucleic acids have become highly effective for monitoring aquatic biodiversity, with an array of suitable use cases, including metrics for fisheries assessment. Traditional methods for assessing fish populations often rely on invasive techniques with limited spatial and temporal coverage. Environmental DNA (eDNA) has revolutionised biomonitoring assessments by facilitating species detection and abundance estimation in a noninvasive and indirect manner. Environmental RNA (eRNA) offers a promising complement by capturing the transcriptional activity of organisms. In addition, the study of eDNA methylation may provide an avenue for detecting the regulation of the expression of genes of interest. This review highlights the opportunities to unlock the full potential of eDNA and eRNA in supporting sustainable fisheries assessment by offering noninvasive, alternative and complementary methods for age assessment, sex identification and reproductive stage, physiological and health status, genetic structure and stock identification. By integrating these innovative approaches with traditional methods, a more comprehensive understanding of aquatic ecosystems can be achieved, ultimately leading to improved fisheries conservation and management decision‐making.

Global Patterns and Gaps in Research on Salinity Tolerance of Inland Fishes - Carlos Cano‐Barbacil; Ignacio Doadrio; Julian D. Olden; Kirk. O. Winemiller; Emili García‐Berthou (Fish and Fisheries, 2026)
Freshwater salinization is an emerging threat impacting approximately one‐third of the world's freshwater bodies. However, the salinity tolerance of many inland fishes remains understudied, despite being a crucial factor in determining species distributions and fitness. We updated and analysed a comprehensive global database of experimental salinity tolerance, compiled from 128 sources, to investigate geographical and taxonomic biases in research on the salinity tolerance of inland fishes. Additionally, we examined how salinity tolerance relates to fish traits and how experimental data align with field‐reported salinity levels. Experimental data on salinity tolerance was available for

Insight into phylogeny of Alburnus (Cypriniformes: Leuciscidae) with zooming in on Peri-Adriatic region - Eleni Anna Charmpila; Radek Šanda; Ivana Buj; Ignacio Doadrio; Silvia Perea; Spase Shumka; Jasna Vukić (Hydrobiologia, 2026)
To date, the phylogeny of Alburnus , one of the most speciose western Palearctic freshwater fish genera, remains unresolved and its monophyly questioned. Here, we present a taxon-dense phylogeny of the genus and related genera, based on mitochondrial and nuclear DNA sequence data. A special focus is put on relationships between the Peri-Adriatic species. Our analyses confirmed the paraphyly of Alburnus with the retrieval of Leucaspius delineatus , Anaecypris punica and Anaecypris hispanica as three separate clades within it. This finding challenges the current taxonomic framework of the genus and highlights the need for a re-evaluation of its classification. The remaining three well-supported clades are currently assigned to Alburnus : Clade I from Levant and the Tigris and Euphrates basins, Clade V with shemayas and Clade VI comprising all remaining species: from Europe, Ponto-Caspian and Aral regions and Anatolia. Most relationships within Clade V and VI were not resolved likely due to rapid diversification in the late Pliocene and Pleistocene. Monophyly of the Peri-Adriatic group, suggested in previous works, was not confirmed. Moreover, Alburnus arborella did not form a monophyletic lineage and displayed extraordinary diversity both in its native and introduced range. Finally, new evidence for introductions of species were provided.

Initiative to stop trade of shark fins within the EU: Is it a good thing for sharks? - José C. Báez; Andrés Domingo; Davinia Torreblanca; Ignacio Doadrio (Marine Policy, 2025)

Prevalent Hybridisation Between Highly Divergent Iberian Chub Species Produces Contrasting Outcomes Across Different Geographic and Time Scales - Sofia L. Mendes; Catarina Bernardo; Silvia Perea; João M. Moreno; Ignacio Doadrio; Philine G. D. Feulner; Carla Sousa Santos; Vitor C. Sousa (Molecular Ecology, 2025)
Genomic data has revealed hybridisation is common in nature. Highly divergent allopatric species are often overlooked in our efforts to characterise the prevalence and consequences of hybridisation in natural systems, presumably because they are viewed as less likely to hybridise. Yet, such species are models to investigate later stages of the speciation continuum. Here, we study such a system—the Iberian chubs ( Squalius spp.), a group of primary fish species with allopatric distributions across distinct environments and river catchments. Throughout their evolutionary history, the rivers inhabited by these species suffered quite dramatic changes, potentially allowing for multiple periods of isolation and secondary contact. To investigate if such a history left traces, we generated low‐coverage whole‐genome resequencing data for 125 individuals from eight Iberian chub species. Our results showed high levels of inter (0.44 ≤ F ST ≤ 0.88) and intra‐specific (0 ≤ F ST ≤ 0.61) genetic differentiation. We uncovered four contrasting cases of potential hybridisation, spanning different geographical and time scales. First, we found evidence of ancient hybridisation on a species now inhabiting a whole river catchment. Second, we uncover recent hybridisation restricted to a localised stream, with introgression of nuclear and mitochondrial DNA. Third, we detected, at a regional scale, a case with nuclear introgression but no detectable mitochondrial DNA introgression. Finally, we uncover a case where two very distinct mitochondrial lineages persist at balanced frequencies in a putative hybrid population, despite no detectable nuclear introgression. Our findings suggest hybridisation and introgression led to assimilation or local exclusion of one or both parental species.

Endemic Neretva bleak, Alburnus neretvae (Cypriniformes: Leuciscidae) from fragile karstic environment: First assessment of the population genetic diversity - Eleni Anna Charmpila; Radek Šanda; Ignacio Doadrio; Silvia Perea; Dario Marić; Dejan Radošević; Jasna Vukić (Biologia, 2025)

Genomic population structure and diversity of the endangered Aphanius iberus: strategies for killifish conservation - Tessa Lynn Nester; Alfonso López-Solano; Silvia Perea; Ignacio Doadrio (Conservation Genetics, 2025)
The evolutionary potential of a species directly impacts its ability to survive in fluctuating environments. A fundamental goal in wildlife conservation is enhancing this potential since anthropogenic pressures and rapid climate change are shifting environments at an alarming rate. One way to increase a species’ adaptive potential is through the delineation of management units based on population genomic analyses. Such units consist of evolutionarily significant gene pools requiring immediate conservation action. The delineation of priority units is fundamental for species on the brink of extinction, a predicament shared by numerous killifish species worldwide which face human-driven habitat transformations leading to the destruction of functioning ecosystems. The Mediterranean coast of the Iberian Peninsula has undergone one of the greatest human-driven habitat transformations in Europe since the turn of the 20th century as a result of agricultural exploitation and urbanization, imposing novel environmental pressures on various aquatic organisms including killifish species, such as the endangered and endemic Spanish toothcarp ( Aphanius iberus Valenciennes, 1846 ). In the present study, we performed a SNP-based genetic analysis to delineate management units, or Operational Conservation Units (OCUs) for A. iberus , sampling a total of 176 individuals from 18 sample locations and analyzing their genetic structure, diversity, levels of gene flow, and degrees of genetic differentiation. Overall, the populations were highly structured with low genetic diversity values. Little to no gene flow was detected and F ST values were high, indicating a large degree of genetic differentiation between populations, most likely attributable to habitat fragmentation. The results of our genetic analyses suggested the recommendation of nine OCUs for A. iberus , which should be implemented immediately into recovery programs to enhance the conservation management of this species. Using A. iberus as a study model, our research exemplifies how to delineate conservation priorities pertinent to killifish species with limited dispersal opportunity as a result of disruptions in population connectivity.

Development and Characterization of Fifteen Polymorphic Microsatellite Loci for Rare and Endangered Species within Luciobarbus Heckel, 1843 Genus in the Aral Basin and Their Conservation Application - Kamila Adyrbekova; Silvia Perea; Ignacio Doadrio (Fishes, 2024)
Biodiversity conservation entails not only the preservation of specific taxa but also genetic diversity. Despite the crucial role of molecular data in freshwater fish conservation management, there is a scarcity of information regarding the genetic diversity of Luciobarbus Heckel, 1843 (Actinopterygii, Cyprinidae) populations in the Aral system. Therefore, the primary aim of this study was to provide genetic information on two native species of the Luciobarbus genus found in the Aral system: L. conocephalus (Kessler, 1872) and L. brachycephalus (Kessler, 1872). These species, like many others in the Aral system, confront the imminent threat of extinction due to system alterations. However, genetic studies on these species at the nuclear level are challenging because Luciobarbus is an allotetraploid genus. Consequently, genetic investigations thus far have focused mainly on sequencing mitochondrial genes due to their haploid nature. This study has successfully developed fifteen new polymorphic microsatellite loci, which can prove to be valuable for population genetics, conservation, and other pertinent research on these species.

Lack of genetic differentiation between two sympatric lacustrine morpho-species within the Astyanax (Characidae: Teleostei) genus, Mexico - Claudia Patricia Ornelas-García; Elena G. Gonzalez; Diethard Tautz; Ignacio Doadrio (Ichthyological Research, 2024)
We analyzed two morpho-species, Astyanax aeneus and Astyanax caballeroi , coexisting in Lake Catemaco, with ecological differences previously associated with different trophic niches. While A. aeneus is a widely distributed species, A. caballeroi is endemic to Lake Catemaco. Due to the contrasting morphology between these two sympatric species, they were originally assigned to different genera, but little is known about their genetic differentiation. We hypothesized that these two species, which present differentiation in morphology and in trophic niches, co-occur in concomitance with assortative mating and form distinct genetic clusters. We tested this prediction by typing a set of 12 microsatellites in 348 individuals of the two morpho-species, comparing their genetic structure patterns with that of an allopatric population of A. aeneus (i.e., the Maquinas population). Genetic structure analysis, assignment analyses, and estimation of gene flow between the sympatric morpho-species were carried out. Contrary to expectations, there is a lack of genetic differentiation between the A. aeneus and A. caballeroi morpho-species. However, there was a genetic differentiation between Lake Catemaco and Río Maquinas populations of A. aeneus . In addition, we found an asymmetric gene flow pattern, with a larger migration rate from A. aeneus to A. caballeroi than in the other direction. Finally, the allopatric population of A. aeneus showed lower levels of genetic diversity than those reported for both morpho-species in the lacustrine system. Consequently, our results support the notion that these morpho-species are either in an early phase of speciation or represent a single polymorphic species. This model provides relevant information to understanding the presence of polymorphisms under gene flow and their potential impact on the speciation process.

Complete mitochondrial genome of the Spanish toothcarp, Aphanius iberus (Valenciennes, 1846) (Actinopterygii, Aphaniidae) and its phylogenetic position within the Cyprinodontiformes order - Alfonso López-Solano; Tessa Lynn Nester; Silvia Perea; Ignacio Doadrio (Molecular Biology Reports, 2023)
Background The Spanish toothcarp ( Aphanius iberus Valenciennes, 1846) is a small fish endemic to the eastern coastline of the Iberian Peninsula and is currently listed as “Endangered” (category IUCN: EN). It mainly inhabits brackish waters which can exhibit large fluctuations in temperature and salinity throughout the year. The genetics of A. iberus are not well-known since most studies have only evaluated the genetic structure of the species under a conservation framework in order to identify its potential conservation units. Different phylogenetic relationships of Aphanius have been published based on some particular genes. In the present study, the entire mitochondrial genome of A. iberus was obtained for the first time in the context of an A. iberus reference genome and a hypothesis regarding its phylogenetic position was considered. Methods and results The mitogenome (a circular doble-stranded DNA sequence of 16,708 bp) was reconstructed and aligned against 83 Cyprinodontiformes and two outgroup taxa to identify the phylogenetic position of A. iberus. PartitionFinder was first used to test for the best evolutionary model and the phylogenetic analyses were performed using two methods: Maximun-Likelihood Approximation (IQ-Tree) and Bayesian inference (MrBayes). Our results show that A. iberus forms a sister group with Orestias ascotanensis, a cyprinodontiform species native to South America. Conclusions The results were congruent with the traditional morphometric reconstructed trees and with a geological vicariant hypothesis involving Cyprinodontiformes where Aphaniidae is shown as a monophyletic family separated from the family Cyprinodontidae. The information gathered from this study is not only valuable for improving our understanding of the evolutionary history of A. iberus , but for future genomic studies involving the species.

The evolutionary journey of freshwater crabs of the genus Potamon (Decapoda: Brachyura: Potamidae) - Hamid Reza Ghanavi; Paniz Rahimi; Mina Tavana; Kamran Rezaei Tavabe; Arash Jouladeh-Roudbar; Ignacio Doadrio (Molecular Phylogenetics and Evolution, 2023)

Mitochondrial genetic diversity, phylogeography and historical demography of Moroccan native freshwater fishes: a case study of the genus Luciobarbus Heckel, 1843 - Keltoum Ouassal; Ignacio Doadrio; Silvia Perea; Miriam Casal-López; Ahmed Yahyaoui; Hassane Jaziri (Biologia, 2022)

High genetic differentiation in the endemic and endangered freshwater fish Achondrostoma salmantinum Doadrio and Elvira, 2007 from Spain, as revealed by mitochondrial and SNP markers - Andrea Corral-Lou; Silvia Perea; Ignacio Doadrio (Conservation Genetics, 2021)

Genetic differentiation among populations of the blackfin goodea Goodea atripinnis (Cyprinodontiformes: Goodeidae): implications for its evolutionary history - Rosa Gabriela Beltrán‐López; Omar Domínguez‐Domínguez; Kyle R. Piller; Humberto Mejía‐Mojica; Adán Fernando Mar‐Silva; Ignacio Doadrio (Journal of Fish Biology, 2021)
Central Mexico is characterized by a complex topography that is the result of historic and contemporary tectonic and climatic factors. These events have influenced the evolutionary history of numerous freshwater fishes in the region. Nonetheless, recent studies have shown that life‐history traits and ecological characteristics of species may influence dispersal capabilities and the degree of genetic connectivity. Goodea (Cyprinodontiformes: Goodeidae) is one of the most widely distributed and environmentally tolerant genera of goodeids. In this study, the authors analysed variation in the mitochondrial cytochrome b gene to evaluate the phylogeographic relationships, genetic structure, genetic diversity and demographic history of Goodea from across its distribution range. They found low genetic differentiation and identified shared haplotypes among several regions. Geographic segregation was found in samples southwest and northeast of the Lower Lerma region, with some internal isolated groups showing phylogeographic differentiation and unique haplotypes. The AMOVA best explained genetic structure when grouped by haplogroups rather than when grouped by recognized biogeographic regions. Several regions showed null genetic diversity, raising the possibility of dispersal mediated by humans. Finally, Bayesian Skyline Plot analysis showed a population expansion for the Southwest haplogroup, except for the Armería population and sub‐group II of the Northeast haplogroup. All this suggests a recent colonization of Goodea atripinnis throughout some of the biogeographic regions currently inhabited by this species.

Multilocus phylogeny and systematics of Iberian endemic Squalius (Actinopterygii, Leuciscidae) - Silvia Perea; Carla Sousa‐Santos; Joana Robalo; Ignacio Doadrio (Zoologica Scripta, 2020)
Inferring the evolutionary history of a group of species can be challenging given the many factors involved. In recent years, the increased availability of sequences of multiple genes per species has spurred the development of new methodologies to analyse multilocus data sets. Two approaches that analyse such data are concatenated supermatrix and coalescent‐based species‐tree analyses. In this study, we used both of these methods to infer the phylogenetic relationships of Iberian species of the genus Squalius from one mitochondrial and six nuclear genes. We found mitonuclear discordance in the phylogenetic relationships of the group. According to the mitochondrial gene analysis, all species were recovered as monophyletic except S. pyrenaicus ; besides, in the concatenated supermatrix analysis of the nuclear markers, this species resolved as polyphyletic with three divergent evolutionary lineages. The coalescent‐based nuclear species‐tree analysis rendered a well‐resolved phylogeny compared with the supermatrix analysis, which was unable to discern between S. carolitertii , S. castellanus and one of the evolutionary lineages of S. pyrenaicus . This result is likely due to the better integration of population uncertainty in the coalescent approach. Furthermore, Bayesian multilocus species delimitation analyses based on a BPP approach strongly supported the distinct nuclear lineages as different species. Nevertheless, the supermatrix analysis was able to obtain well‐supported relationships in the divergent lineages with low numbers of individuals. Our study highlights the usefulness of different analytical methodologies to obtain a more complete picture of the evolutionary history of taxa, especially when discordant patterns among genes are found.

Evolutionary history of the genus Gobiomorus Lacépède 1800 (Teleostei: Eleotridae) - SESANGARI GALVAN-QUESADA; Ignacio Doadrio; Omar Domínguez-Domínguez (Frontiers in Marine Science, 2019)

Freshwater fishes of the Maghreb: distribution, diversity and conservation status - Matthew Ford; Amina Brahimi; Ignacio Doadrio; Silvia Perea; Ahmed Yahyaoui; Jörg Freyhof (Frontiers in Marine Science, 2019)

Phylogeography and demographic history of Eleotridae fishes from Tropical Eastern Pacific - SESANGARI GALVAN-QUESADA; VICTOR PIÑEROS; OMAR DOMINGUEZ-DOMINGUEZ; IGNACIO DOADRIO VILLAREJO (Frontiers in Marine Science, 2019)

Adaptive radiation of labeobarbs (Labeobarbus; Cyprinidae) in the Genale River, East Africa: is this pure sympatric speciation? - Boris Levin; Miriam Casal-López; Evgeniy Simonov; Yury Dgebuadze; Nikolai Mugue; Alexei Tiunov; Ignacio Doadrio; Alexander Golubtsov (Frontiers in Marine Science, 2019)

The Messinian imprint on the evolution of freshwater fishes of the genus Luciobarbus Heckel, 1843 (Teleostei, Cyprinidae) in the western Mediterranean - Miriam Casal‐López; Ignacio Doadrio (Journal of Biogeography, 2018)
Aim The current configuration of the Mediterranean Basin is the result of a complex geological history that promoted a drastic change of biological diversity, richness and distribution of freshwater organisms. Currently cyprinids of the genus Luciobarbus are the only representative of primary freshwater fishes widely distributed in the Mediterranean Basin, showing its highest diversity in the Western Mediterranean. Within this context, our objective was to explore the biogeographical patterns of the genus Luciobarbus in the context of the drastic geological changes during the Messinian. Location Western Mediterranean, including southern Iberia and North Africa. Methods Sampling covered the range of all known populations of Luciobarbus present in North Africa and southern Iberian Peninsula. Molecular data included mitochondrial and nuclear markers ( mt‐cyb and actin II ). Time‐calibrated phylogenies were inferred and a dispersal–extinction–cladogenesis model was used to reconstruct the biogeographical history. Results Our results suggest that the two western lineages of Luciobarbus originated during the Messinian, one including most of the North African species from Morocco and western Algeria and another composed of Iberian, one Moroccan and one Algerian species. Main conclusion During the Messinian, we found that two main events shaped the distribution of the western lineages of Luciobarbus . The first is associated with the end of the Messinian, which has previously been claimed to explain the difference between sister groups of freshwater fish fauna from both sides of the Gibraltar Strait. The second older and previously undetected event is associated with the existence of the last gateways connecting the Mediterranean Sea and the Atlantic Ocean.

Factors shaping contemporary patterns of genetic diversity of the Portuguese endemic cyprinids - Sousa Santos Carla; Robalo Joana; Pereira Ana; Branco Paulo; Santos José; Ferreira Maria; Sousa Monica; Doadrio Ignacio (Frontiers in Marine Science, 2016)

Phylogeographic analysis of genus Herichthys (Perciformes: Cichlidae), with descriptions of Nosferatu new genus and H. tepehua n. sp. - Mauricio De la Maza-Benignos; Claudia Patricia Ornelas-García; María de Lourdes Lozano-Vilano; María Elena García-Ramírez; Ignacio Doadrio (Hydrobiologia, 2015)

Assessing population status of Parachondrostoma arrigonis (Steindachner, 1866), threats and conservation perspectives - Carles Alcaraz; Gerard Carmona-Catot; Pilar Risueño; Silvia Perea; Cristina Pérez; Ignacio Doadrio; Enric Aparicio (Environmental Biology of Fishes, 2015)

Comparative population genetic structure and demographic patterns of two killifish species (Aphanius baeticus and Aphanius iberus) at the Iberian Peninsula - Gonzalez Elena; Pedraza Carlos; Cunha Carina; Oliva-Paterna Francisco; Torralva Mar; Doadrio Ignacio (Frontiers in Marine Science, 2015)

Different population structure in genus Luciobarbus Heckel, 1843 (Actinopterygii, Cyprinidae) on both sides of the Strait of Gibraltar - Casal-Lopez Miriam; Perea Silvia; Doadrio Ignacio; Yahyaoui Ahmed (Frontiers in Marine Science, 2015)

Phylogeography, historical demography and distribution modelling of freshwater fishes inhabiting seasonally fluctuating Mediterranean river systems: a case study using the Iberian cyprinid Squalius valentinus - Perea Silvia; Doadrio Ignacio (Frontiers in Marine Science, 2015)

Critically endangered species facing range retreats are not necessarily genetically depleted: the case of the endemic freshwater fish Anaecypris hispanica (Steindachner, 1866) - Sousa-Santos Carla; Robalo Joana; Francisco Sara; Carrapato Carlos; Cardoso Ana; Doadrio Ignacio (Frontiers in Marine Science, 2015)

Mitochondrial phylogeography of the killifish Aphanius fasciatus (Teleostei, Cyprinodontidae) reveals highly divergent Mediterranean populations - Venera Ferrito; Anna Maria Pappalardo; Adriana Canapa; Marco Barucca; Ignacio Doadrio; Ettore Olmo; Concetta Tigano (Marine Biology, 2013)

From the mountains to the sea: phylogeography and cryptic diversity within the mountain mullet, A gonostomus monticola ( T eleostei: M ugilidae) - Caleb D. McMahan; Matthew P. Davis; Omar Domínguez‐Domínguez; Francisco J. García‐de‐León; Ignacio Doadrio; Kyle R. Piller (Journal of Biogeography, 2013)
Aim The mountain mullet, A gonostomus monticola , is a diadromous fish widespread throughout M iddle A merica, occurring in rivers along the A tlantic and P acific slopes, as well as in the W est I ndies. Based on the disjunct distribution of this species, it has been hypothesized that this fish may represent more than one taxon. The purpose of this study was to conduct a robust phylogeographical analysis of A . monticola across its range, using mitochondrial and nuclear markers. We aimed to investigate the potential for cryptic diversity and the time‐scale of divergence in an effort to elucidate biogeographical episodes within M iddle A merica in relation to the evolutionary history of A gonostomus monticola . Location North and M iddle A merica, including the W est I ndies. Methods Mitochondrial and nuclear sequence data (cyt b , S7 ‐1) from individuals throughout the range of the species were analysed phylogenetically using maximum‐likelihood methodology. The oldest known fossil mullet was used as a calibration to investigate divergence times for clades within A . monticola . Results Results indicate four distinct lineages within the known range of A . monticola that largely correspond to oceanic basins ( C aribbean, G ulf of M exico, P acific‐A, P acific‐B). Divergence time estimates indicate early to mid‐ M iocene divergences for all four A . monticola clades, with O ligocene to M iocene divergences of internal nodes. Main conclusions These findings are congruent with geological hypotheses regarding movement of the C hortís block, as well as recent studies on the age of beginning emergence of the P anama A rc.

Biogeography of the Mesoamerican Cichlidae (Teleostei: Heroini): colonization through the GAARlandia land bridge and early diversification - Oldřich Říčan; Lubomír Piálek; Rafael Zardoya; Ignacio Doadrio; Jan Zrzavý (Journal of Biogeography, 2013)
Aim We present a molecular phylogenetic and biogeographical analysis of the Mesoamerican cichlid fishes (Cichlidae: Cichlasomatinae: Heroini), a dominant part of the freshwater biodiversity of the region. Based on these analyses we investigate the spatial and temporal origins and diversification of the group. Location Mesoamerica. Methods Model‐based phylogenetic methods ( MrBayes ) using seven molecular markers with a virtually complete species‐level taxon sampling, together with the Bayesian approach to statistical dispersal–vicariance analysis (S‐ DIVA ), and fossil‐ and palaeogeography‐calibrated beast molecular clock analyses were used to assess the timing of dispersal, vicariance and diversification events. Results We present a robust multigene phylogeny resolved from the deepest nodes to the species level. Two colonizations of Middle America and one of the Greater Antilles occurred from South America within a narrow time window during the Oligocene epoch. Cichlid colonization of Central America proceeded from the north in the Early–Middle Miocene. Central America later became repeatedly fragmented during the latter half of the Miocene, which led to the formation of the present ichthyological provinces prior to the final closure of the Panama Isthmus. Main conclusions The heroine cichlid fishes colonized the Greater Antilles and Middle America simultaneously through the GAAR landia land bridge during the Oligocene. Central America (including eastern Panama) was colonized from northern Middle America in the Early–Middle Miocene. Thus our results do not support a direct colonization of Middle America from South America, or a Cretaceous–Palaeocene colonization through the proto‐Antilles, or a colonization of the Greater Antilles from Middle America as suggested by previous studies.

50,000 years of genetic uniformity in the critically endangered Iberian lynx - RICARDO RODRÍGUEZ; OSCAR RAMÍREZ; CRISTINA E. VALDIOSERA; NURIA GARCÍA; FERNANDO ALDA; JOAN MADURELL‐MALAPEIRA; JOSEP MARMI; IGNACIO DOADRIO; ESKE WILLERSLEV; ANDERS GÖTHERSTRÖM; JUAN LUIS ARSUAGA; MARK G. THOMAS; et al. (Molecular Ecology, 2011)
Low genetic diversity in the endangered Iberian lynx, including lack of mitochondrial control region variation, is thought to result from historical or Pleistocene/Holocene population bottlenecks, and to indicate poor long‐term viability. We find no variability in control region sequences from 19 Iberian lynx remains from across the Iberian Peninsula and spanning the last 50 000 years. This is best explained by continuously small female effective population size through time. We conclude that low genetic variability in the Iberian lynx is not in itself a threat to long‐term viability, and so should not preclude conservation efforts.

Genetic relationships of brook lamprey of the genus Lampetra in a Pyrenean stream in Spain - Ana M. Pereira; Vítor C. Almada; Ignacio Doadrio (Ichthyological Research, 2011)

Biogeography of Iberian freshwater fishes revisited: the roles of historical versus contemporary constraints - Ana F. Filipe; Miguel B. Araújo; Ignacio Doadrio; Paul L. Angermeier; Maria J. Collares‐Pereira (Journal of Biogeography, 2009)
Aim The question of how much of the shared geographical distribution of biota is due to environmental vs. historical constraints remains unanswered. The aim of this paper is to disentangle the contribution of historical vs. contemporary factors to the distribution of freshwater fish species. In addition, it illustrates how quantifying the contribution of each type of factor improves the classification of biogeographical provinces. Location Iberian Peninsula, south‐western Europe ( c . 581,000 km 2 ). Methods We used the most comprehensive data on native fish distributions for the Iberian Peninsula, compiled from Portuguese and Spanish sources on a 20‐km grid‐cell resolution. Overall, 58 species were analysed after being categorized into three groups according to their ability to disperse through saltwater: (1) species strictly intolerant of saltwater (primary species); (2) species partially tolerant of saltwater, making limited incursions into saltwaters (secondary species); and (3) saltwater‐tolerant species that migrate back and forth from sea to freshwaters or have invaded freshwaters recently (peripheral species). Distance‐based multivariate analyses were used to test the role of historical (basin formation) vs. contemporary environmental (climate) conditions in explaining current patterns of native fish assemblage composition. Cluster analyses were performed to explore species co‐occurrence patterns and redefine biogeographical provinces based on the distributions of fishes. Results River basin boundaries were better at segregating species composition for all species groups than contemporary climate variables. This historical signal was especially evident for primary and secondary freshwater fishes. Eleven biogeographical provinces were delineated. Basins flowing to the Atlantic Ocean north of the Tagus Basin and those flowing to the Mediterranean Sea north of the Mijares Basin were the most dissimilar group. Primary and secondary freshwater species had higher province fidelity than peripheral species. Main conclusions The results support the hypothesis that historical factors exert greater constraints on native freshwater fish assemblages in the Iberian Peninsula than do current environmental factors. After examining patterns of assemblage variation across space, as evidenced by the biogeographical provinces, we discuss the likely dispersal and speciation events that underlie these patterns.

Molecular characterisation and recent evolution of myxoma virus in Spain - Fernando Alda; Tania Gaitero; Mónica Suárez; Ignacio Doadrio (Archives of Virology, 2009)

Diversification within glacial refugia: tempo and mode of evolution of the polytypic fish Barbus sclateri - HUGO F. GANTE; JOANA MICAEL; FRANCISCO J. OLIVA‐PATERNA; IGNACIO DOADRIO; THOMAS E. DOWLING; MARIA JUDITE ALVES (Molecular Ecology, 2009)
A diversity of evolutionary processes can be responsible for generating and maintaining biodiversity. Molecular markers were used to investigate the influence of Plio‐Pleistocene climatic oscillations on the evolutionary history of taxa restricted to the freshwaters of a classical glacial refugium. Population genetic, phylogenetic and phylogeographical methods allowed the inference of temporal dynamics of cladogenesis and processes shaping present‐day genetic constitution of Barbus sclateri , a polytypic taxon found in several independent river drainages in southern Iberian Peninsula. Results from different analyses consistently indicate several range expansions, high levels of allopatric fragmentation, and admixture following secondary contacts throughout its evolutionary history. Using a Bayesian demographical coalescent model on mitochondrial DNA sequences calibrated with fossil evidence, all cladogenetic events within B. sclateri are inferred to have occurred during the Pleistocene and were probably driven by environmental factors. Our results suggest that glaciation cycles did not inhibit cladogenesis and probably interacted with regional geomorphology to promote diversification. We conclude that this polytypic taxon is a species complex that recently diversified in allopatry, and that Pleistocene glaciation–deglaciation cycles probably contributed to the generation of biological diversity in a classical glacial refugium with high endemicity.

Historical biogeography of European leuciscins (Cyprinidae): evaluating the Lago Mare dispersal hypothesis - André Levy; Ignacio Doadrio; Vítor C. Almada (Journal of Biogeography, 2009)
Aim To test the importance of the Lago Mare stage of the Messinian Salinity Crisis for the dispersal and diversification of European leuciscins (Cyprinidae: Leuciscinae). Location Europe. Methods Cytochrome b sequences of European leuciscins were employed to investigate phylogenetic relationships among species, using Bayesian inference, and to estimate times of diversification, using a relaxed molecular clock. The distributions of 190 European leuciscins were compiled, and regional species compositions were compared using a taxonomic similarity index and an area cladogram. Results Leuciscins restricted to the Iberian and Italian peninsulas and the West and South Balkan regions are phylogenetically more closely related to northern European species than to species from another southern European area. Application of a relaxed molecular clock to a Bayesian phylogeny indicates that most southern clades originated and diversified prior to the Messinian. Southern European regions are taxonomically distinct from one another, and from a more taxonomically homogeneous group of areas that includes Anatolia, East Balkans, Middle East, North Europe and West Russia. Main conclusions The scenario of a Messinian period of dispersal of Paratethyan fauna into Mediterranean regions, via the Lago Mare, predicts a rapid period of diversification and a pattern of close association among southern European faunas. Phylogenetic relationships among leuciscins, the timing of cladogenic events, and the taxonomic similarity among geographical regions do not conform to this expectation. The depth of clades endemic to southern Europe, together with the high levels of endemism in these regions, suggests that the faunas in these regions diverged prior to the Messinian and have evolved largely in isolation from one another. Our results support a model of gradual colonization of Mediterranean regions since the Oligocene. Subsequent connections between adjacent areas may have occurred in the Messinian or Pleistocene.

Threatened fishes of the world: Achondrostoma occidentale Robalo, Almada, Sousa-Santos, Moreira & Doadrio 2005 (Cyprinidae) - Joana I. Robalo; Carla Sousa-Santos; Ignacio Doadrio; Vítor C. Almada (Environmental Biology of Fishes, 2008)

Human Impacts on Drainages of the Mesa Central, Mexico, and Its Genetic Effects on an Endangered Fish, Zoogoneticus quitzeoensis - OMAR DOMÍNGUEZ‐DOMÍNGUEZ; LUIS BOTO; FERNANDO ALDA; GERARDO PÉREZ‐PONCE DE LEÓN; IGNACIO DOADRIO (Conservation Biology, 2007)
The Mesa Central of Mexico is of special conservation interest due to its high richness of freshwater fish species, of which the goodeines are one of the most representative groups. Through an integrated approach, we determined conservation priorities for goodeine populations. We based our recommendations on the genetic diversity (variation in five microsatellite DNA loci) in 10 populations of Zoogoneticus quitzeoensis and on an analysis of ecological (e.g., presence of exotic species), social (e.g., political situation), and environmental (e.g., pollution) information for 52 historical occurrence points for species in the genus Zoogoneticus . Patterns of genetic erosion and genetic diversity indices were closely associated with human impact. Recent bottleneck events were most evident in the populations from remnants of the lakes drained at the beginning of the twentieth century. We identified seven operational conservation units (OCUs), all of which should be conserved because they contain unique portions of the total variation of the species. Special attention needs to be given to increase genetic variability, recover population sizes, and reestablish contact among populations within OCUs. It is imperative to create an integrative and effective approach for the recovery and conservation of the freshwater fish diversity of Central Mexico that is based on social and natural sciences.

Historical biogeography of some river basins in central Mexico evidenced by their goodeine freshwater fishes: a preliminary hypothesis using secondary Brooks parsimony analysis - Omar Domínguez‐Domínguez; Ignacio Doadrio; Gerardo Pérez‐Ponce de León (Journal of Biogeography, 2006)
Aims Our aim was to uncover and describe patterns of historical biogeography of the main river basins in central Mexico, based on a secondary Brooks parsimony analysis (BPA) of goodeine fishes, and to understand the processes that determine them with respect to the molecular clock of the goodeines and the geological events that have taken place in the region since the Miocene. Location The region covered in this study includes central Mexico, mostly the so‐called Mesa Central of Mexico, an area argued to be a transitional zone comprising several major river drainages from their headwaters at high elevations along the Transmexican Volcanic Belt to the coast of the Gulf of Mexico and the Pacific Ocean. Methods Based on a previous phylogenetic hypothesis regarding the Goodeidae, we built a data matrix using additive binary coding. First, we conducted a primary BPA to provide general explanations of the historical biogeography of Central Mexico. As ambiguity was found, a secondary BPA was conducted, and some areas were duplicated in order to explain the reticulated history of the area. Area cladograms were obtained by running a parsimony analysis. Instances of vicariance and non‐vicariance processes were described with reference to the cladogram obtained from secondary BPA. Results The study area was divided into 18 discrete regions. Primary BPA produced nine equally parsimonious cladograms with 129 steps, and a consistency index (CI) of 0.574. A strict consensus cladogram shows low resolution among some areas, but other area relationships are consistent. For secondary BPA, five of the 18 regions were duplicated (LEA, COT, AYU, CUT, PAN); one was triplicated (BAL); and one was quadruplicated (AME), suggesting that the pattern of distribution of species in these areas reflects multiple independent events. These areas correspond with the regions exhibiting the highest levels of diversification and the most complex geological history, and those for which river piracy events or basin connections have been proposed. The secondary BPA produced a single most parsimonious cladogram with 118 steps, and a CI of 0.858. This cladogram shows that none of the duplicated areas are nested together, reinforcing the idea of a reticulated history of the areas and not a single vicariant event. Main conclusions Although our results are preliminary and we cannot establish this as a general pattern, as the BPA is based on a single‐taxon cladogram, resolution obtained in the secondary BPA provides some insights regarding the historical biogeography of this group of fishes in river basins of central Mexico. Secondary BPA indicates that the historical biogeography of central Mexico, as shown by their goodeine freshwater fishes, is complex and is a result of a series of vicariant and non‐vicariant events such as post‐dispersal speciation and post‐speciation dispersal.

Threatened Fishes of the World: Aphanius baeticus (Doadrio, Carmona & Fernández Delgado, 2002) (Cyprinodontidae) - Francisco J. Oliva-Paterna; Ignacio Doadrio; Carlos Fernández-Delgado (Environmental Biology of Fishes, 2006)

Threatened Fishes of the World: Leuciscus carolitertii Doadrio, 1988 (Cyprinidae) - José A. Carmona; Ignacio Doadrio (Environmental Biology of Fishes, 2000)

Distribution Patterns of Indigenous Freshwater Fishes in the Tagus River Basin, Spain - José A. Carmona; Ignacio Doadrio; Ana L. Márquez; Raimundo Real; Bernard Hugueny; Juan M. Vargas (Environmental Biology of Fishes, 1999)

Threatened fishes of the world: Barbus comiza Steindachner, 1865 (Cyprinidae) - Ignacio Doadrio; Anabel Perdices (Environmental Biology of Fishes, 1998)

Threatened fishes of the world: Cobitis calderoni Bacescu, 1961 (Cobitidae) - Anabel Perdices; Ignacio Doadrio (Environmental Biology of Fishes, 1997)

Threatened fishes of the world: Cobitis paludica (De Buen, 1930) (Cobitidae) - Anabel Perdices; Ignacio Doadrio (Environmental Biology of Fishes, 1997)